Correlation analysis of the relationship between B-type natriuretic peptide and selected echocardiographic parameters in patients with permanent pacemakers - Sielski, Janusz; Grabowska, Urszula; Kaziród-Wolski, Karol; Matejko, Maria (Medical Studies/Studia Medyczne, 2015)
Introduction: The present study was undertaken to evaluate the practical value of BNP measurements and echocardiographic left ventricular volume index in patients with permanent pacemakers because there are no such reports in the literature. Aim of the research: The aim of the study was to reveal multiple correlations between BNP levels and selected echocardiographic parameters of the left atrium in patients with permanent pacemakers. In the literature there are reports on the significance of BNP values and left atrial size in patients with permanent pacemakers. The results of the present study appear to be of value in the outpatient assessment of these patients. Material and methods: We analysed a group of 117 patients with permanent pacemakers (AAI/R 21 patients, DDD/R 59 patients, VVI/R 37 patients) and 48 healthy volunteers serving as the control group. BNP measurements were performed on venous blood samples using Triage meters. The Simpson method and the ellipse method were used to assess the left atrium on echocardiography. Results: There was a significant correlation between BNP and maximum left atrial volume, minimum left atrial volume, and left atrial volume index in patients with AAI/R, DDD/R, and VVI/R pacemakers at 3 and 6 months after the implantation. Conclusions : In patients after implantation of permanent pacemakers there are correlations between BNP values and echocardiographic left atrial parameters, especially in patients with DDD/R pacemakers. Left atrial function improves in patients with DDD/R pacemakers. Pacemaker check-up should be extended to include BNP measurements and echocardiographic assessment of the left atrium.